AN ANALYSIS OF HERMIONE GRANGER IN HARRY POTTER AND THE PRISONER OF AZKABAN MOVIE - Tarisa Ramadhania Hakim; Eusabinus Bunau; Dwi Riyanti (LPPM Universitas PGRI Jombang, 2024)
This article aims to describe the character traits of Hermione Granger in Harry Potter and the Prisoner of Azkaban movie and to emphasize Hermione Granger’s character to be an exemplification for students. The researcher used qualitative method to analyze the data to reveal meaningful insights from Hermione Granger’s traits. The findings show that there are ten traits found in the Harry Potter and the Prisoner of Azkaban movie, such as alert, bold, sharp-witted, caring, compassionate, curious, determined, knowledgeable, observant, and sympathetic. The most prominent trait is sharp-witted with thirteen appearances. Afterward, the ten character traits of Hermione Granger are related to three descriptors of the (FFM). Three traits fit to openness, conscientiousness, and agreeableness factor. Hermione Granger is a character who can serve as a role model for students since her virtues can be used as an example of how hard work, commitment, and enthusiasm for learning can lead to becoming successful.